Peran Brand Image dan Kualitas Produk terhadap Switching Behavior Pengguna iPhone dalam Perspektif Islam - Aminda, Laras Ayu; Setiawan, Agus; Ligery, Finny; Mushodiq, M. Agus (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the influence of brand image and product quality on the switching behavior of iPhone users, while incorporating Islamic values as an ethical framework in consumer behavior. The research background is based on the increasing dynamics of brand switching among younger generations, particularly in the highly competitive smartphone industry. The study employed a quantitative approach with data collected through non-participant observation and structured questionnaires, covering respondent demographics, brand image, product quality, and switching tendencies. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression to examine the relationships among variables. The findings reveal that brand image does not have a significant effect on switching behavior, while product quality emerges as the dominant factor influencing consumers’ decisions to remain loyal or switch to alternative brands. Simultaneously, brand image and product quality were found to exert a significant interactive effect on switching behavior, indicating their complementary roles in shaping consumer perceptions. From an Islamic perspective, the findings underscore that brand image and product quality should align with the principles of honesty, fairness, and compliance with halal–tayyib standards. The integration of functional and ethical aspects is thus essential not only for reducing switching behavior but also for fostering sustainable consumer loyalty.